Experimental study of the effect of temperature on the drying process and volume shrinkage of oats - Domenico, Camila Nicola Boeri Di; Serafini, Laís Fabiana; Bavaresco, Maurício (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
This study aimed to determine the effect of air temperature on the drying kinetics and volume shrinkage of oat grains. Grains with an initial moisture content of 17% (db) were selected and dried in a forced air circulation oven under three temperature conditions: 65, 75 and 85ºC. To ascertain the volume shrinkage, the grains were dried in trays and then placed in a graduated cylinder. Volume reduction of the grains was monitored throughout the drying process. As the temperature of the drying air increased, the time of the reduction process decreased. The rate of volume shrinkage decreased during drying and this effect was intensified with increasing temperature.